2014
DOI: 10.1016/j.jbiotec.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Switching an anti-IgG binding site between archaeal extremophilic proteins results in Affitins with enhanced pH stability

Abstract: As a useful reagent for biotechnological applications, a scaffold protein needs to be as stable as possible to ensure longer lifetimes. We have developed archaeal extremophilic proteins from the “7 kDa DNA-binding” family as scaffolds to derive affinity proteins (Affitins). In this study, we evaluated a rational structure/sequence-guided approach to stabilize an Affitin derived from Sac7d by transferring its human IgG binding site onto the framework of the more thermally stable Sso7d homolog. The chimera obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…We previously reported that Sac7d and Sso7d are highly resistant from low to high pH1213, and here, we confirm this as a general property of the “7 kDa DNA-binding” proteins. This is interesting considering that the pH inside Sulfolobus cells is about 6.55 while the pH outside is 3.533, suggesting there has been no selection pressure for these pH resistances.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We previously reported that Sac7d and Sso7d are highly resistant from low to high pH1213, and here, we confirm this as a general property of the “7 kDa DNA-binding” proteins. This is interesting considering that the pH inside Sulfolobus cells is about 6.55 while the pH outside is 3.533, suggesting there has been no selection pressure for these pH resistances.…”
Section: Discussionsupporting
confidence: 89%
“…Also, a smaller size is interesting for in vivo applications, such as imaging and therapy, as it allows a better diffusion across barriers or to reach tumors for example44. Up to now, Sac7d and Sso7d have been used as scaffolds to design Affitins13212425. However, this study teaches us that Sto7 and Aho7c should be a good basis to generate more robust Affitins.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously described Affitins as artificial affinity proteins derived from the archaeal extremophilic 7 kDa DNA‐binding proteins, such as Sac7d and Sso7d (Béhar et al, ; Krehenbrink et al, ; Mouratou et al, ; Pecorari & Alzari, ). Recently, we have also extensively characterized this family of proteins (Kalichuk et al, ).…”
Section: Discussionmentioning
confidence: 99%